Capulopsyche keralensis gen. et sp. nov., a new genus and species of the subfamily Taleporiinae (Lepidoptera: Psychidae) from Kerala, India - Unnikrishnan, Usha Ayyath; Sobczyk, Thomas; Jose, Roby Thekkudan; Jose, Joyce (Zootaxa, 2023)
A new genus and species, Capulopsyche keralensis gen. et sp. nov. from the subfamily Taleporiinae is described from Kerala, India. The new genus has distinct features from other genera of the subfamily. Double-walled larval case architecture is one of the unique characteristics of this genus. Details of life stages, distribution, COI sequencing, and the morphology of adults are described in the paper.